2022
DOI: 10.1111/ajt.16988
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-suppressor CXCR5+CD8+ T cellular therapy ameliorates antibody-mediated rejection following kidney transplant in CCR5 KO mice

Abstract: CCR5 KO kidney transplant (KTx) recipients are extraordinarily high alloantibody producers and develop pathology that mimics human antibody‐mediated rejection (AMR). C57BL/6 and CCR5 KO mice (H‐2b) were transplanted with A/J kidneys (H‐2a); select cohorts received adoptive cell therapy (ACT) with alloprimed CXCR5+CD8+ T cells (or control cells) on day 5 after KTx. ACT efficacy was evaluated by measuring posttransplant alloantibody, pathology, and allograft survival. Recipients were assessed for the quantity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Additionally, alloprimed CXCR5 + CD8 + T cells from CCR5 KO recipients have a 30% lower capacity to kill antibody-producing IgG + B cells in vitro compared with WT CXCR5 + CD8 + T cells. 19 ACT with CD8 + T Ab-supp cells in high alloantibody-producing CCR5 KO KTx recipients significantly reduces alloantibody production (4.6-fold reduction of day 14 posttransplant alloantibody titer) and ameliorates AMR pathology (2.4-fold reduction in day 14 composite AMR pathology score). Furthermore, ACT-mediated reduction of alloantibody titer and improved pathology correlates with enhanced allograft survival in murine KTx recipients (median survival time = day 52 versus day 15 without ACT).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, alloprimed CXCR5 + CD8 + T cells from CCR5 KO recipients have a 30% lower capacity to kill antibody-producing IgG + B cells in vitro compared with WT CXCR5 + CD8 + T cells. 19 ACT with CD8 + T Ab-supp cells in high alloantibody-producing CCR5 KO KTx recipients significantly reduces alloantibody production (4.6-fold reduction of day 14 posttransplant alloantibody titer) and ameliorates AMR pathology (2.4-fold reduction in day 14 composite AMR pathology score). Furthermore, ACT-mediated reduction of alloantibody titer and improved pathology correlates with enhanced allograft survival in murine KTx recipients (median survival time = day 52 versus day 15 without ACT).…”
Section: Introductionmentioning
confidence: 95%
“…These results complement our prior studies reporting the antigen specificity of alloprimed CXCR5 + CD8 + T-cell effector function. 18,19 We next examined the expression of the cytotoxic effector molecules previously reported to be important for antibody-suppressor CXCR5 + CD8 + T function. 33 To do this, CXCR5 + CD8 + T cells were retrieved from alloprimed GFP mice for adoptive transfer into CCR5 KO KTx recipients.…”
Section: Cni Impairs Act-mediated In Vivo Cytotoxicity Targeting Allo...mentioning
confidence: 99%
See 1 more Smart Citation
“…They also used human CXCR5 murine leukemia virus (MuLV)-based retroviral expression vector to insert CXCR5 gene to CD8 + T cells, and the expression of PD-1 was downregulated, that could be associated with the homing of remodeled-Tfc cells into B cell follicles (22). As for the potential therapeutic modalities in antibody mediated disease, Zimmerer et al (83) found that after receiving adoptive therapy with alloprimed CXCR5 + CD8 + T cells, the alloantibody titer in kidney transplant mice was reduced, which ameliorated antibody-mediated rejection and prolonged allograft survival.…”
Section: Genetic Engineering and Adoptive Therapymentioning
confidence: 99%
“…As for the potential therapeutic modalities in antibody mediated disease, Zimmerer et al. ( 83 ) found that after receiving adoptive therapy with alloprimed CXCR5 + CD8 + T cells, the alloantibody titer in kidney transplant mice was reduced, which ameliorated antibody-mediated rejection and prolonged allograft survival.…”
Section: Treatment Prospectsmentioning
confidence: 99%